Development of a comprehensive model of self-assessment in a high er education institution - Vera-Silva, Andrea del Pilar; Castiblanco-Jimenez, Ivonne Angelica; Cruz-Gonzalez, Joan Paola (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Quality in higher education is estimated by quality assurance systems using self-assessment processes. Higher Education Institutions (HEIs) conceive it as a stakeholders’ active participation process of identifying strengths and possibilities for improvement both for institutions and for academic programs aimed at the fulfillment of their mission and continued improvement. This research seeks to respond to the selfassessment processes contained in Colombian legislation by integrating the self-assessment models and requirements of the ISO 9001:2015 standard defined by the International Organization for Standardization. To this end, the Schnarch’s product development method is applied in the development of a comprehensive model of self-assessment for the Colombian School of Engineering Julio Garavito. This study allowed for a characterization and diagnosis of the self-assessment process by stakeholders through the system dynamics methodology in order to develop a model enabling HEIs to address self-regulation, government approval, and institutional and academic programs accreditation processes, as well as their respective renewals.